Suche oko u alergika – jak unikać, jak leczyć? - Groblewska, Anna; Bogacka, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Allergic conjunctivitis and dry eye are major ocular surface disorders affecting millions of people. Although neither of them is a sight-threatening disease, they have a serious impact on patients’ quality of life. A typical clinical symptom of allergic conjunctivitis is itching, whereas the symptoms of dry eye are burning sensation, irritation or ocular fatigue, but allergic conjunctivitis and dry eye sometimes share very similar symptoms. Allergies are often associated with ocular surface diseases and in particular with dry eye syndrome. Reduced quantity or quality of tears increases the number of allergens, limits their evacuation through the canaliculi and increases inflammation, which is an aggravating factor for allergy. Allergic eye diseases, even SAC, are associated with advanced tear instability and thickening of the lipid layer of the tear film. In allergic conjunctivitis we observed decreased break-up time caused in part by decreased goblet cell density. Severe allergies may cause permanent dry eye state and sometimes the exact frontier between the two pathologies is unknown. It is obvious that both cause inflammation and both aggravate each other. Patients with dry eye tend to develop more eye allergies; they may not have a sufficiently large tear volume to wash the allergen out quickly enough to prevent the symptoms of allergy. Patients with both dry eye and allergy should be treated for both concomitantly, because treating only one may not produce the desired results. Tear film disturbances, inflammatory damage of the conjunctival epithelium and sometimes conjunctival fibrosis may be produced by eye drop preservatives; artificial tears with safe preservative or preservative-free drops should be used. Even the newer systemic antihistamines through action on the muscarinic-3 receptors reduce tear production from the lacrimal glands and mucin secretion from the goblet cells, so when used, additionally artificial tears should be applied locally.